The Influencing Effect of Silver Nitrate Fillers on the hardness of Flexible Resin - Huda Abed Hasson; Lateef Essa Alwan (Journal of Techniques)
The development of polymer chemically produces alternative materials to polymethyl methacrylate, such as nylon, and epoxy resin, these resins are modified by thermoplastic process, and This Received The disadvantage of acrylic resin is the colonization of microorganism growth of fungi and candida adhesion. This study is designed to evaluate and compared the consequence of silver nitrate fillers reinforcement Accepted flexible acrylic hardness as one of the mechanical properties to find the effect of various concentrations.  A (0.1and 0. 2) ml of the filler (silver nitrate) additive to the flexible acrylic.